Políticas públicas voltadas para a conservação da fauna marinha brasileira - Silva, Luana Caroline Costa (2023)
Environmental legislation was created to support public policies capable of reconciling nature conservation with socioeconomic development, but its effectiveness has been little evaluated in marine ecosystems. This theme is addressed in this thesis over three chapters. In the first chapter, the level of legal certainty and biological coverage of the legislation was estimated through the search for marine species in legal instruments produced since 1960. 443 official instruments were found, 87% of which were ordinances, normative instructions and decrees, considered weak in the legal point of view. Laws, resolutions and the Federal Constitution represented only 12%. Only 138 species were listed in 352 instruments, representing just 7% of the diversity of marine animals recognized by the Brazilian government. Marine invertebrates, although very diverse, were the least protected. It was concluded that legislation has grown since 1960, is broad, but legally weak and biologically limited. In the second chapter, it was investigated whether one of the best conservationist public policies – the creation of Marine Protected Areas (MPAs) under the terms of Federal Law No. 9985/2000 – is functioning as a repository of endangered species. The number of endangered species of the 68 federal marine MPAs was related to the unit's size, age, category and management descriptors. It was observed that full protection MPAs with a management plan had a higher number of endangered species, but more recent MPAs protected fewer endangered species than the old ones. The effectiveness index, annual visitation rate and size of the MPA did not significantly affect its number of threatened species. Although the survey results indicate that Brazilian MPAs serve as a repository of endangered species, they reveal serious bottlenecks in the management of official databases, dissemination of information to society and monitoring of biodiversity. In the third chapter, we sought to assess the potential of participatory monitoring of endangered marine megafauna species, as provided in Normative Instruction No. 2/2022 of ICMBio (Monitor Program). For two years (2019-2021), ten artisanal fishermen from three fishing communities on the coast of Paraíba carried out on-board monitoring of the animals during their fisheries. 460 sightings of 567 animals were recorded over 196 expeditions carried out by monitor fishermen. The most sighted animals were turtles (89% of records) and dolphins (10% of records), but there were also four sightings of humpback whales and one manatee. Some challenges were identified during the study, such as the abandonment of the project by four volunteers; low proportion of animals taxonomically identified at the species level (32%); and lack of financial resources for continued monitoring. Despite the challenges, it was concluded that there is a high potential for artisanal fishermen to act as monitors of marine biodiversity. As a summary of the thesis, it is concluded that Brazilian public policies need to be improved, expanded and fully implemented to guarantee the socioeconomic development of the country in line with the conservation of its rich marine fauna.